Cost-Benefit Implications in the Emerging Electronic Banking Space in Nigerian Financial Sector - Hyginus I. Ihenetu; Augustine A. Anaele (International Journal of Regional Development, 2021)
The paper evaluated the cost-benefit implications in the emerging electronic banking space in Nigerian financial sector. Data were collected from CBN statistical bulletin and NDIC annual report. Twenty one (21) banks operating in Nigeria constitutes the population of the study and sample size of twelve (14) years was selected through purposive sample method. Auto-Regressive Distributive Lag (ARDL) was used to analyze the data after stationarizing it through Augumented Dicky Fuller (ADF) unit root test. The findings show that ATM, POS and MB have no significant effect while WIT has negative significant on banks’ profit. The findings further reveal that the combination of these variables has positive and significant effect on banks’ profit. We therefore recommend that banks should fully utilize the benefits provided through electronic banking by ensuring that more ATM terminals are provided in order to reduce crowd. Professionals that can constantly put the machine in order should be emlpoyed and there should be constant money in the machine to enable the banks make more profits and serve the people better at all times. POS should be made available to the users and at a reduced cost without hidden charges to enable people of different categories have access to them. This will help to generate revenue to the banks and reduce their cost of transaction etc.